"No Official Help Is Available"—Experience of Parents and Children With Congenital Heart Disease During COVID-19. Issue 4 (July 2021) - Marino, L. V.; Wagland, R.; Culliford, D. J.; Bharucha, T.; Sodergren, S. C.; Darlington, Anne-Sophie E.
Introduction: The purpose was to explore the experience, information and support needs, and decision-making of parents of children with congenital heart disease (CHD), as well as the children/young people themselves, during the COVID-19 crisis. Materials and Methods: A survey study of parents of children with CHD, children and young people, capturing experiences, decision-making, information, and support needs during the COVID-19 crisis was conducted. The survey launched for one month (April 9, 2020) during the first infection wave in the United Kingdom and subsequent restriction of free movement under lockdown rules from March 23, 2020, until May 31, 2020. Results: One hundred eighty-four parents and 36 children/young people completed the survey. Parents were more likely to worry about the virus (86.4%) than children/young people (69.4%), while (89%) parents were more vigilant for symptoms of the virus versus children/young people (69.4%). A thematic analysis of the qualitative comments covered 34 subthemes, forming eight overarching themes: Virus—(1) risk of infection; (2)information, guidance, and advice; (3) change in health care provision; and (4) fears and anxieties, and lockdown and isolation—(5) psychological and social impact, (6) keeping safe under lockdown, (7) provisions and dependence on others, and (8) employment and income. Conclusions: There was widespread concern over the virus especially among parents. Parents and children/young people, however, were frustrated with the lack of specific and pediatric-focused information and guidance, expressing disappointment with the adult-centric information available. Parents also felt alone, especially with their concerns around the implications of cardiac service suspension and the implication for their child's health. In order to better support children and their families, resources need to be developed to address families' and children/young people's concerns for their health during this pandemic.